2021
DOI: 10.1021/acsmedchemlett.1c00272
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a First-in-Class Inhibitor of the Histone Methyltransferase SETD2 Suitable for Preclinical Studies

Abstract: SET domain-containing protein 2 (SETD2), a histone methyltransferase, has been identified as a target of interest in certain hematological malignancies, including multiple myeloma. This account details the discovery of EPZ-719 , a novel and potent SETD2 inhibitor with a high selectivity over other histone methyltransferases. A screening campaign of the Epizyme proprietary histone methyltransferase-biased library identified potential leads based on a 2-amidoindole core. Structure-based dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…In our recent report on the discovery of the SETD2 inhibitor tool compound EPZ-719, we focused primarily on exploration of the structure–activity relationship (SAR) with respect to the indole motif and the central core of the molecule, leading to SETD2 inhibitor 2 and the closely related analogues 3 and 3-F (see Figure 1 ). 14 The unique binding mode of these aniline-containing inhibitors was also disclosed in that report. Anilines are prevalent in modern drug discovery screening libraries because of their ease of synthesis, but this structural motif tends to impart less-than-ideal pharmacokinetic properties and potential metabolism-derived toxicities.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…In our recent report on the discovery of the SETD2 inhibitor tool compound EPZ-719, we focused primarily on exploration of the structure–activity relationship (SAR) with respect to the indole motif and the central core of the molecule, leading to SETD2 inhibitor 2 and the closely related analogues 3 and 3-F (see Figure 1 ). 14 The unique binding mode of these aniline-containing inhibitors was also disclosed in that report. Anilines are prevalent in modern drug discovery screening libraries because of their ease of synthesis, but this structural motif tends to impart less-than-ideal pharmacokinetic properties and potential metabolism-derived toxicities.…”
mentioning
confidence: 68%
“…During analogue design, compounds biased to reside in the cis conformation were prioritized because the cocrystal structure of 3 suggested that this would best mimic the planar aromatic ring seen in the early leads 2 and 3 ( Figure 1 ). 14 Subsequent conformational analysis showed that cis -cyclohexanes would have a strong energetic bias to reside in conformer I , thereby avoiding 1,3-diaxial strain from the 1,3-disubstitution ( Figure 2 ), and this was supported by molecular dynamics simulations. Molecular modeling predicted conformer I to bind well in the ligand pocket compared with the trans -cyclohexane in conformers III and IV , where the conformational changes of the ligand binding site would be less tolerated because of the axial substituent (see the Supporting Information ).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Given the observation that H3K27me3 aberrantly spreads into H3K36 methylated regions, we tested whether inhibition of SETD2, the only known methyltransferase to deposit H3K36me3 and a PRC2 antagonist, could enable H3K27me3 spreading and halt DLBCL proliferation. We treated a panel of EZH2-wt and -mutant lymphoma cell lines with SETD2-IN-1, a recently disclosed, selective SETD2 inhibitor ( 30 ). Of the seven EZH2-mutant cell lines tested, six were sensitive to SETD2-IN-1 in comparison to only one of the four EZH2-wt cell lines ( Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, the targeting of SETD2 is a potential candidate for combination therapies with Tip60 or ATM inhibitors, which can become novel therapeutic strategies for cancer treatment. Recently, a fist-in-class inhibitor, EPZ-719, was reported and is in preclinical validation studies [ 53 ].…”
Section: Histone Methylationmentioning
confidence: 99%